Kalman Filter Photovoltaic Power Prediction Model Based on Forecasting Experience - Yang, Ying; Yu, Tianyang; Zhao, Weiguang; Zhu, Xianhui (Frontiers in Energy Research, 2021)
A Kalman filter photovoltaic (PV) power prediction model based on forecasting experience is proposed to solve the problem that the accuracy of the prediction method based on historical experience is reduced under anomalous situations. This paper uses the hourly solar irradiance forecasting model, numerical weather prediction (NWP) data and the photoelectric conversion model to calculate the ground irradiance and PV power generation, which are used as the forecasting experience data. The dynamic equation of Kalman filter model is obtained by fitting the forecasting data to make the prediction model with the future situation information properties while solving the modeling difficulties caused by the transcendental equation characteristic of the photoelectric conversion model. In the iterative process of Kalman filter algorithm, the measured power is used to correct the prediction error and signiﬁcantly limit the error variability, so as to realize the ultra-short-term accurate prediction of PV power, ultimately improve the management of PV energy storage power stations. The comparative analysis through DKASC data simulation verifies that the results show that the proposed model is effective and can achieve better results in predictive accuracy.